Emotional Mental Problems among Adolescents: Urban and Semi-Urban Settings - Meita Dhamayanti; Stanza Uga Peryoga; Mohamad Rizqy Firmansyah (Althea Medical Journal, 2018)
Background: Emotional mental problems refer to something that complicates someone in an attempt to conform to the environment and experiences. In Indonesia the prevalence of emotional mental problems is 6.0%. In West Java province as the most populous region in Indonesia, the number of prevalence is above the national average of 9.3%. West Java province was selected for this study because in addition to being the most densely populated region, it also has urban and semi-urban areas. The purpose of this study was  to identify the difference in the prevalence of emotional mental problems of adolescent in urban and semi-urban areas.Methods: This study used the cross sectional approach method. Inclusion criteria were adolescents aged 14-16 years who attended several Junior High and Senior High Schools in Cirebon City as an urban area and Sumedang Regency as a semi-urban area. Exclusion criteria were adolescents who filled out  the questionnaire incompletely. The study variables consisted of adolescents, urban and semi-urban areas, and emotional mental problems. Data were analyzed by using chi square (x2) test.Results: Out of 1039 respondents, 816 met the inclusion criteria. There were significant differences in emotional mental problems on the aspects of emotional symptoms, behavior, hyperactivity, interpersonal relationships, social behavior, and total value of emotional mental problems with p value <0.05.Conclusions: There is a difference in emotional mental problems of adolescents in urban and semi-urban areas. Adolescents in urban regions have higher mental-emotional problems than in semi-urban regions.